Il corpo della differenza: una questione costituzionale nella prospettiva dell’analisi di genere (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Considering bodies and their sexual differences in relation to biolaw, the essay moves from the theoretical perspective of a gender analysis oriented by the “principle of gender non-subordination”, as typically expressed by the Italian Constitution. Being the issue of human reproduction paradigmatic both in terms of bio-law and in terms of gender, it calls for investigating whether and how far complementarity in the sex-gender system has been considered, when addressing the issue of reproduction (and, in particular, abortion and IVF) and when shaping its legal categories and institutions. In conclusion, the judgement n. 272/2017 of the Constitutional Court, which deals with children born by surrogate motherhood abroad, is critically reviewed, looking at a broader understanding of what we call “birth’s truth” and questioning the legal ban of surrogacy in the light of new principle of “birth mother’s acknowledgement”.
Keywords: Biolaw; constitutional principle of gender non-subordination; sex-gender system; motherhood; surrogacy